Transiently antigen primed B cells can generate multiple subsets of memory cells. - Jackson S Turner; Zachary L Benet; Irina Grigorova (PLoS ONE, 2017)
Memory B cells are long-lived cells that generate a more vigorous response upon recognition of antigen (Ag) and T cell help than naïve B cells and ensure maintenance of durable humoral immunity. Functionally distinct subsets of murine memory B cells have been identified based on isotype switching of BCRs and surface expression of the co-stimulatory molecule CD80 and co-inhibitory molecule PD-L2. Memory B cells in a subpopulation with low surface expression of CD80 and PD-L2 are predominantly non-isotype switched and can be efficiently recruited into germinal centers (GCs) in secondary responses. In contrast, a CD80 and PD-L2 positive subset arises predominantly from GCs and can quickly differentiate into antibody-secreting plasma cells (PCs). Here we demonstrate that single transient acquisition of Ag by B cells may be sufficient for their long-term participation in GC responses and for development of various memory B cell subsets including CD80 and PD-L2 positive effector-like memory cells that rapidly differentiate into class-switched PCs during recall responses.